XPS of quaternary ammonium and phosphonium ionic liquids - Blundell, Rebecca K. (2016)
X-ray Photoelectron Spectroscopy (XPS) has been used to probe the influence of cation structure on fundamental interactions within Ionic Liquid (IL) systems. A series of tetraalkylammonium-based ILs and their phosphonium analogues have been investigated. A robust C 1s peak fitting model has been developed and described for the tetraalkylphosphonium and tetraalkylammonium families of ionic liquid, with comparisons made between the two series. Cation-anion interactions have been investigated to determine the impact of changing the cationic core from nitrogen to phosphorus on the electronic environment of the anion. Comparisons between long and short chain cationic systems, and the effect of cation conformational restriction, are also described. Additionally, a high-energy Ag Lα’ X-ray source has been utilised to probe the structure of the IL/vacuum interface using Energy-resolved XPS (ERXPS) for tetraalkylammonium- and tetraalkylphosphonium-based ILs, with comparison made to data obtained with Angle-resolved XPS (ARXPS) experiments using a standard Al Kα X-ray source. The capability of the Ag Lα’ source for IL analysis is confirmed, alongside the characterisation of previously undetected high energy core level photoelectron emissions. The effect of cation functionalisation is also studied by XPS, with a view to establish fine-tuning of charge transfer from anion to cation using electron-withdrawing substituents embedded within the alkyl side chain of the cation. Binding energy analysis indicated cation functionalisation had minimal influence on the electronic environment of the ionic head groups with respect to the non-functionalised analogues. The performance of ILs, with respect to cation functionalisation, as solvents in the Suzuki reaction is also reported in this Thesis, whereby evidence is provided for changing the nature of catalysis via cation functionalisation.